Pemaknaan Nilai-Nilai Nahdlatul Ulama (NU) dalam Desa Tradisional dan Perumahan Modern (Studi Kasus: Desa Sekarpuro dan Perumahan Bukit Az-Zikra Sentul) - Aisha, Sarah; Suprapti, Atiek; Sardjono, Agung Budi; Indraswara, Mohammad Sahid (Nature : National Academic Journal of Architecture, 2025)
This study explains that religion-based housing has significantly developed in Indonesia; however, the integration of local Islamic organizational traditions into modern housing and traditional villages has not been widely explored. The aim of this research is to identify the manifestation of Islamic values in the Nahdlatul Ulama (NU) village of Sekarpuro and in the Bukit Az-Zikra Housing, Sentul. A comparative case study approach is used, employing Henri Lefebvre’s theory of the production of space as the analytical framework. Data collection techniques include participatory observation, in-depth interviews with housing managers, religious leaders, and residents, as well as document analysis of relevant regulations and policies. The findings reveal a significant difference in spatial formation: the NU village of Sekarpuro organically embodies Nahdlatul Ulama values through historical social practices, while Bukit Az-Zikra Housing produces space through planned design by a foundation authority. The study concludes that the presence of central religious figures and strong community networks are key to the successful manifestation of NU values. The theoretical contribution of this research lies in the development of Lefebvre’s spatial theory by adding local cultural dimensions as a significant factor in the production of religious value-based space.